MODEL KOMUNIKASI PELAYANAN PUSTAKAWAN TERHADAP PEMUSTAKA DI DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI SULAWESI TENGGARA. - Siska Yulianti (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2017)
The problem of this research is how communication model of Librarian Service to Library in Library Service and Archives Prov. Southeast Sulawesi. The purpose of this study is to find out how the communication model of librarian services to the librarian in the Library Service and Archives Prov. Southeast Sulawesi. The research was conducted at the Library and Filing Service of Southeast Sulawesi Province. This research method is descriptive qualitative with descriptive method. The technique of determining informants is done by purposive sampling or direct determination by the researcher to be informant, data collection is done through observation, interview, and documentation at the Library and Filing Service of Southeast Sulawesi Province. The results of this study indicate that the communication model of librarian services to the librarian in the Library and Filing Service of Southeast Sulawesi Province is a one-way communication, two-way communication and effective multi-direction communication, which can be concluded based on the results of interviews librarians and librarians in the Library and Archives Southeast Sulawesi Province. Keywords: Librarian, Library.